2020
DOI: 10.1074/jbc.ra120.015273
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced enzyme kinetics of reverse transcriptase variants cloned from animals infected with SIVmac239 lacking viral protein X

Abstract: HIV Type 1 (HIV-1) and simian immunodeficiency virus (SIV) display differential replication kinetics in macrophages. This is because high expression levels of the active host deoxynucleotide triphosphohydrolase  sterile alpha motif  domain and histidine-aspartate  domain-containing protein 1 (SAMHD1) depletes intracellular dNTPs, which restricts HIV-1 reverse transcription, and results in a restrictive infection in this myeloid cell type. Some SIVs overcome SAMHD1 restriction using viral protein X (Vpx), a vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The authors compared RT sequences isolated from these monkeys at 6 to 7 months postinfection (mpi) and at 36 mpi, and found an enhanced accumulation of mutations in RT genes from samples infected with virus lacking Vpx. Biochemical analysis revealed that at 36 mpi, RT variants from (−)Vpx viruses displayed higher catalytic and nucleotide incorporation efficacies compared to RTs from (+)Vpx virus-infected animals or compared to samples from early time points [106]. These findings corroborate the idea that lentiviruses without a Vpx-like function may have evolved more efficient RT molecules to enable cDNA synthesis in nondividing cells.…”
Section: "Super-rt": Highly Efficient Lentiviral Reverse Transcriptasessupporting
confidence: 62%
See 3 more Smart Citations
“…The authors compared RT sequences isolated from these monkeys at 6 to 7 months postinfection (mpi) and at 36 mpi, and found an enhanced accumulation of mutations in RT genes from samples infected with virus lacking Vpx. Biochemical analysis revealed that at 36 mpi, RT variants from (−)Vpx viruses displayed higher catalytic and nucleotide incorporation efficacies compared to RTs from (+)Vpx virus-infected animals or compared to samples from early time points [106]. These findings corroborate the idea that lentiviruses without a Vpx-like function may have evolved more efficient RT molecules to enable cDNA synthesis in nondividing cells.…”
Section: "Super-rt": Highly Efficient Lentiviral Reverse Transcriptasessupporting
confidence: 62%
“…In 2011, it became clear that lentiviruses, such as HIV-2 and several SIV strains, counteract SAMHD1 with the help of their accessory proteins Vpx and Vpr, resulting in the proteasomal degradation of SAMHD1 [54][55][56]89,96]. Another strategy to evade the dNTPase activity of SAMHD1, found in HIV-1 and other SIVs, is the use of highly efficient RTs that function at low dNTP concentrations in the presence of SAMHD1 [104][105][106]. In contrast, herpesviruses employ their conserved serine/threonine kinases to phosphorylate and inactivate SAMHD1 [73][74][75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increased efficiency allows the virus to bypass SAMHD1 restriction and replicate in the low-dNTP-pool conditions of macrophages [ 166 ]. Furthermore, RTs from SIVmac239 (Vpx-) infections acquire numerous amino-acid mutations that result in enhanced RT kinetics compared to RTs from SIVmac239 (Vpx+) infections [ 167 ]. This suggests that the loss of Vpx during an in vivo SIVmac239 infection can drive RT variations to counteract the limited availability of dNTPs in macrophages [ 167 ].…”
Section: Host and Viral Proteins’ Evolution Due To The Host–pathogen ...mentioning
confidence: 99%